Retarded Field Energy Analyzer as a tool to Study the Ion Velocity Distribution Functions on Radio Frequency Argon Plasma in Expanding Magnetic Field at Low Pressures - Mishra, L.N. (Journal of Nepal Physical Society, 2016)
Plasma expanding in the space along the magnetic filed is well known phenomenon. This plasma device was constructed to investigate the space plasma in laboratory in connection with plasma flows, electron distribution, ion distribution, instability and turbulence. For this purpose, the low-temperature plasma is produced by means of a 13.56 MHz Helicon plasma source at 300-1000 W rf power. The plasma is expanding from the 13.5 cm diameter source into a 150 cm long chamber of 60 cm diameter. Ion energy and its velocity distribution produced by a current-free double layer at the expansion region have been studied by means of retarding field energy analyzers. Furthermore, the effects due to the geometrical shape of the expanding magnetic field in plasma flows have also been investigated. Journal of Nepal Physical Society Vol.3(1) 2015: 82-88